Antimicrobial property of date seed extract - Mirghani, Mohamed Elwathig Saeed; Mikail, Maryam Abimbola; Adewale, Ahmed Idris; Mohamed Ismail, Abdul Karim; Daoud, Jamal Ibrahim (IIUM Press, 2011)
Twelve extracts from four solvents (ethanol, methanol, acetone and distilled water) and three varieties of date palm seeds (Deglet Nour, Biruni and Mixture) were tested in vitro for their antimicrobial activity against two Gram-positive (Staphylococcus aureus and Bacillus subtilis) and two Gram-negative (Escherichia coli, Pseudomonas aeruginosa) bacteria species to establish whether or not they have antimicrobial activity. The central composite design was used to investigate the effects of three independent variables (extraction temperature, extraction time and agitation speed) on the dependent variable (inhibition zone). All the twelve extracts of date palm seeds inhibited all the test microorganisms with minimum inhibitory concentration ranging from 10 to 42mg/ml and with minimum bactericidal concentration ranging from 21 to 167mg/ml. Extraction temperature, agitation, and extraction time significantly affected total antimicrobial contents extracted from date seeds.